The study on the live streaming frequency strategy choices of streamers in live E-commerce - Yingjing Wu; Ying Cui (PLoS ONE, 2025)
Live-streaming e-commerce, emerging as a novel business model, has garnered considerable attention from leading platforms and brands. It not only exerts a profound influence on consumers’ lifestyles and consumption habits but also presents brand owners with a fresh sales model. This paper focuses on the perspective of the live-streamer and explores the scenario where a live-streamer sells two competing products through live shows. By constructing three models—single live show, two live shows with information disclosure, and two live shows without information disclosure—it is discovered that, when the proportion of fans for the live-streamer is relatively low, the live-streamer opts for the two live shows strategy without information disclosure. When fan percentage is elevated and product competition diminishes, the streamer consistently favors the single live-show strategy. As the proportion of fans is moderate and product competition diminishes, the streamer increasingly favors a two live show strategy that includes disclosed product information. Furthermore, when the live show interval is short and the proportion of live-streamer fans is small, the live-streamer prefers to adopt the two live show strategies without product information disclosure; when the live show interval is long, the live-streamer prefers the two live show strategies under product information disclosure. When there is a high proportion of fans, regardless of the length of the interval between the two live shows, the live-streamer prefers the single live show strategy.